Financial Literacy, Efficacy, Stress, and Credit Behavior among Medical Students in Banyumas Regency, Indonesia - Stefani Widodo (Journal of Economics, Social, and Humanities, 2024)
This study examines the relationship between financial literacy, financial efficacy, financial stress, and credit behavior among Banyumas Regency, Indonesia medical students. The research aims to understand how these factors interact and influence the financial decision-making of students in a high-pressure academic environment. Data were collected through an online survey targeting medical students with experience in consumer credit, and responses were analyzed using SEM-PLS methods. The results show that financial literacy does not significantly influence credit behavior directly, nor does financial efficacy mediate the relationship between financial literacy and credit behavior. However, financial stress was found to play a significant moderating role, demonstrating its critical influence on students' financial decisions. These findings highlight the importance of addressing psychological factors like stress and enhancing financial literacy and efficacy. The study provides practical implications, suggesting the need for tailored financial education programs that integrate stress management strategies to equip medical students better to handle financial challenges. These interventions can foster responsible credit behavior and financial stability by addressing knowledge gaps and emotional burdens. This research contributes to the broader understanding of financial decision-making, emphasizing the interconnectedness of financial knowledge, self-efficacy, stress, and behavior, particularly in the unique context of medical students. Future studies are encouraged to explore these relationships in other high-stress academic or professional environments to enhance the understanding of financial behavior dynamics further.